2019
DOI: 10.1002/pc.25419
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mechanical and thermal properties of polyurethane‐imide foams with the addition of expended vermiculite

Abstract: Polyurethane‐imide (PUI) foams, in combination with the mechanical performance of polyurethane and flame retardancy of polyimide, were prepared by polyimide prepolymer method. Expended vermiculite (EV), with a wider layer spacing than vermiculite, was used as the filler to further enhance the mechanical and thermal properties of the PUI foams. The effect of filler content on the morphology of foams was also investigated. The results showed that the mean cell diameter of foams became smaller and the cell size d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…By increasing the filler loading, more bulky foam was obtained and the amount of residual char increased parallel with the TGA results. As reported in the literature, 22,28,67,7177 incorporation of VMT led to increase in the flame spread resistance and some important reasons were underlined as follows. As known, VMT is a natural mineral that mostly composed of SiO 2 , Al 2 O 3 , Fe 2 O 3 .…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…By increasing the filler loading, more bulky foam was obtained and the amount of residual char increased parallel with the TGA results. As reported in the literature, 22,28,67,7177 incorporation of VMT led to increase in the flame spread resistance and some important reasons were underlined as follows. As known, VMT is a natural mineral that mostly composed of SiO 2 , Al 2 O 3 , Fe 2 O 3 .…”
Section: Resultsmentioning
confidence: 78%
“…72,73 It was also reported that foamy morphology functioned as a barrier layer for delaying the spread of the flame by minimizing the air contact that also led to decrease in heat transfer. 22,28,67,71–78…”
Section: Resultsmentioning
confidence: 99%
“…In addition, vermiculite particles act like a barrier, which hinder leaving the volatile gases from the material and retard the decomposition processes. 54…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the polyimide-based foam preserved the original structure, revealing its prominent high temperature resistance. Because of this excellent heat resistance performance, the polyimide foam materials have been widely used in navigation, aviation, and other fields. Therefore, it can be concluded that the as-prepared polyimide-based foam has outstanding combustion resistance performance. Interestingly and meaningfully, Zhang et al investigated the relationship between thermal conductivity, flexibility, and density of the 3D hybrid foams (Figure a–e) .…”
Section: Multifunctional Properties and Relevant Mechanisms Of Polyim...mentioning
confidence: 99%